PENGARUH SUHU DAN LAMA PENYIMPANAN TERHADAP KANDUNGAN VITAMIN C DALAM CABAI MERAH (Capsicum annuum. L) DAN AKTIVITAS ANTIOKSIDANNYA - Aqnes Budiarti; Dyah Ayu Elisa_Kurnianingrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACTVitamin C is known as an antioxidant. The vitamin C level in food can be affected by temperature and prolonged storage. Red chili (Capsicum annum L) could be decomposed due to storage. This study aims to investigate the influence of temperature and storage time to the vitamin C level in red chili and its antioxidant activity. The determination of vitamin C level used a spectrophotometric method and the antioxidant activity assay using DPPH method. Red chili was storage in 0 (zero) days, three (3) days and 7 (seven) days. Storage temperature varies at 0⁰C; 10⁰C and room temperature. Data were analyzed statistically with a linearity test and model polynomial regression (curve) with a 95% confidence level. The results showed that the duration of storage significantly influenced the vitamin C level in red chili and its antioxidant activity. Contrary to the duration of storage, the storage temperature had no effect on the vitamin C level and antioxidant activity in red chili. The vitamin C level and antioxidant activity was highest in the storage 0 (zero) days that were the vitamin C level of 0.24% w/w and antioxidant activity of 35.58%. Keywords: Temperature and prolonged storage, red chili, antioxidant activity, DPPH